2003
DOI: 10.1037/0022-006x.71.6.1036
|View full text |Cite
|
Sign up to set email alerts
|

Project Genesis: Assessing the Efficacy of Problem-Solving Therapy for Distressed Adult Cancer Patients.

Abstract: The efficacy of problem-solving therapy (PST) to reduce psychological distress was assessed among a sample of 132 adult cancer patients. A second condition provided PST for both the patient and a significant other. At posttreatment, all participants receiving PST fared significantly better than waiting list control patients. Further, improvements in problem solving were found to correlate significantly with improvements in psychological distress and overall quality of life. No differences in symptom reduction … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
255
2
6

Year Published

2008
2008
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 291 publications
(271 citation statements)
references
References 51 publications
6
255
2
6
Order By: Relevance
“…Our findings are also not consistent with previous reports, suggesting that the effect of cognitive-behavioral therapy may become more prominent over longer follow-up times [2,25]. An explanation may be that the physical training intervention in the present trial comprised a self-management approach.…”
Section: Discussioncontrasting
confidence: 99%
See 2 more Smart Citations
“…Our findings are also not consistent with previous reports, suggesting that the effect of cognitive-behavioral therapy may become more prominent over longer follow-up times [2,25]. An explanation may be that the physical training intervention in the present trial comprised a self-management approach.…”
Section: Discussioncontrasting
confidence: 99%
“…This problemsolving training showed to have beneficial short-and longterm effects for cancer survivors in quality of life [25]. Furthermore, it has been effectively applied for a variety of mental health problems, such as depression and anxiety, and medical conditions including diabetes, back pain, arthritis, hypertension, headaches, and obesity [10,23].…”
Section: Interventionmentioning
confidence: 99%
See 1 more Smart Citation
“…Six studies compared the couples intervention with a patient-only intervention [35,36,37,38,39,40], eight studies used a patient-only comparison group and a usual care control group [41,42,43,44,45,46,47,48], one study compared two types of couples interventions with a patient-alone comparison group [49], and the remaining twenty compared a couples intervention with usual care or waiting-list controls. Twenty-eight studies reported effect sizes, or provided information to calculate effect sizes.…”
Section: Main Descriptivesmentioning
confidence: 99%
“…Interventions using CBST improved somatic/ physical outcomes including symptom perception [41,42,63,61,48], fitness/ muscle strength [49], sexual limitation [64], physical Quality of Life (QOL) [61], Cholesterol [34], and fear of movement [48]. In comparison with a patient-only/ control group, CBST interventions enhanced behaviours such as dyadic coping [43], medication adherence [65], and increased dietary self-efficacy and spousal support [59].…”
Section: Effect Of Cbst On Patient/ Partner Outcomesmentioning
confidence: 99%